Benthic foraminiferal diversity in the Arabian Gulf: spatial patterns in a basin-wide assessment - Abduljamiu Olalekan Amao; Khalid Al-Ramadan; Michael Kaminski; Fabrizio Frontalini (PLoS ONE, 2025)
Benthic foraminifera play crucial roles in marine ecosystems and serve as valuable bioindicators of ecological conditions and environmental changes. Despite their importance, comprehensive basin-wide assessments of their diversity patterns remain scarce, particularly in complex environments like the Arabian Gulf. This study reveals the variation of benthic foraminiferal diversity within the gulf and provides insights into its distribution patterns and relationships with environmental gradients. We compiled a comprehensive dataset of benthic foraminiferal occurrences from published literature and public databases, encompassing more than 492 species from nine orders, 39 superfamilies, 89 families, and 150 genera. Using an ensemble of species distribution models, we modelled the spatial patterns of individual species and stack these predictions to estimate foraminiferal species richness across the basin. We documented a pronounced north-south diversity gradient that differs from typical latitudinal patterns observed in larger marine systems. Our methodological framework identifies bathymetry and dissolved oxygen as primary drivers of foraminiferal distributions when averaged across all species, with significant influence from iron concentration and salinity. However, individual species showed diverse environmental responses, with variables of lower mean importance often exerting primary control on specific taxa, highlighting the ecological specialization that enables such high diversity in this extreme environment. The east-west diversity gradient reveals the impact of basin-scale circulation patterns on foraminiferal assemblage composition, a phenomenon relevant to other semi-enclosed seas worldwide. The models show high performance (mean AUC > 0.94, TSS > 0.8, Kappa > 0.82), demonstrating the potential of this approach in capturing complex species-environment relationships. Additionally, model predictions align well with known foraminiferal distributions and diversity patterns reported in previous studies across the gulf. This study provides the first basin-wide assessment of benthic foraminiferal diversity in the Arabian Gulf, revealing complex spatial patterns and environmental relationships. Most significantly, our delineation of species-specific ecological niches provides a valuable framework for forecasting foraminiferal responses to climate-driven environmental changes, particularly thermal stress, which our models identify as more influential in its extreme rather than mean values.